KINERJA NELAYAN TERIPANG DALAM MENINGKATKAN PENDAPATANNYA DI PULAU PUTRI KECAMATAN RAAS KABUTAN SUMENEP MADURA JAWA TIMUR - jurnalpps pps; Cathrine Sri Hartati; Woro Utari; Hariyanto ÔÇì (Jurnal Manajerial Bisnis, 2020)
ABSTRACT In the Madura area, they should be provided with appropriate equipment so that the utilization of unexplored resources can be more optimal, also open new jobs so as to enable the absorption of labor for the people around, considering that the production process is very necessary for labor and is ultimately expected to increase welfare in the community on the island of princess Madura. This study aims to analyze the performance of sea cucumber fishermen in increasing their income in Putri Island, Raas District, Sumenep Madura. East Java. Data analysis used was quantitative and quantitative by collecting data using interviews and questionnaires. The results showed that 1) Teripang Fisherman Performance on the island of Raas Madura increased to 3.8 with a percentage, 5%; 2) The income of sea cucumber fishermen on the princess island of Raura Madura is able to meet their daily needs; 3) Internal and external factors are factors that encourage and hinder the success of sea cucumber fishermen on the island of Raas Madura. With a percentage of 60% Good performance factor and 40% Ugly Performance Factor; 4) Implementation of a precise strategy can increase the performance and income of sea cucumber fishermen on the island of Raas Madura until it reaches 5%. Keywords : performance improvement, sea cucumber fishermen income